A novel UHPLC-MS/MS method for the determination of four α-dicarbonyl compounds in wine and dynamic monitoring in human urine after drinking. (January 2023) - Qi, Chao; Jin, Yueying; Cheng, Shengyu; Di, Lei; Wang, Xin; Zhang, Minghui; Zhang, Lingli; Li, Xi-Ling; Han, Yu; Ma, Qingkun; Min, Jun Zhe
Graphical abstract: Highlights: A mass spectrometry probe was developed for detecting carbonyl functional groups. We established an effective method for analyzing GO, MG, DMGO, and 3-DG in wine. Our method captured the metabolic dynamics in the human body after drinking wine. Abstract: α-dicarbonyl compounds (α-DCs) serve as potential biomarkers for oxidative stress-related diseases but are difficult to detect. To study the metabolism of carbonyl compounds, we developed a new mass spectrometry probe, 3-benzyl-2-oxo-4λ 3 -thiazolidine-4-carbohydrazide (BOTC), containing hydrazyl groups for the targeted detection of carbonyl functional groups. In a novel approach, we used BOTC pre-column derivatization with ultrahigh performance liquid chromatography–tandem mass spectrometry (UHPLC-MS/MS) to simultaneously detect four kinds of α-DCs in red wine as well as in urine after drinking. The α-DCs were completely separated (R 2  ≥ 0.9995), detection was sensitive (detection limit was 12.5–50 fmol), consistent (intraday and interday precision was 0.1–5.7 %), and efficient (average recoveries were 103.3–110.2 %). The method was applied to the analysis of α-DCs in different wines and the dynamic monitoring of transit and excretion in vivo after drinking. Our novel method provides a new strategy for the detection of α-dicarbonyl compounds in red wine and dicarbonyl compounds produced in oxidative stress-related diseases.